27. STUDY ON EPIDEMIOLOGICAL CHARACTERISTICS OF DEMENTIA AMONG THE ELDERLY PEOPLE IN NGHE AN PROVINCE (2022 - 2023) (Vietnam Journal of Community Medicine, 2024)
Objective: Several epidemiological characteristics of dementia in the elderly of Nghe An Province (2022-2023).Method: Analyzing cross-sectional study.Results: 2202 patients being investigated have an average age of 69.7 ± 7.36; the male and female ratio: 1.43/1; Education levels of respondents: Literacy rate: 8.4%, Elementary level: 24.5%, Secondary level: 47.2%, High school level and above: 19.9%. The proportion of elderly suffering from dementia in general of Nghe An Province: 6.1%; Literacy rate: 13.0%, Elementary level: 9.6%, Secondary level: 4.9%, High school level and above: 1.6%. The proportion of people suffering from dementia shows an upward trend according to the age brackets: 60-64: 2.5%; 65-69: 4.4%; 70-74: 5.8%; 75-79: 7.6%; 80-84: 15.6%, 85-89: 16.9%, 90-102: 26.3%. The proportion of people suffering from dementia according to gender: Male 6.2% and Female: 6.0%.Conclusion: The prevalent of elderly people having dementia in Nghe An Province in 2022 - 2023 was 6.1%. The prevalent of cases rose according to age brackets. The lower the education level among people, the higher the tendency to be detected with dementia.
Keywords: dementia; elderly people